Action of sedative drugs for the development of delirium and functional profile of patients admitted to intensive care units (Research, Society and Development, 2021)
Introduction: Sedatives are drugs used as therapeutic aid in patients under intensive care. Among the possible controversial outcomes for its use, cognitive changes are punctuated in the literature, with acute encephalopathy or delirium, being the most described. Objectives: To evaluate the association between the use of drugs with sedative action for the development of delirium and to characterize the functional profile of individuals with delirium. Material and Methods: Longitudinal study, carried out in a public hospital in the state network, from June 2019 to October (first half) of 2020, with individuals over 18 years old, admitted to intensive care units and infirmaries, for scales for assessing sedation, delirium and functionality (Richmond Agitation Sedation Scale - RASS, Confusion Assessment Method for the Intensive Care Unit - CAM-ICU and Status Score for the Intensive Care Unit - FSS, respectively), with verbalization and without admission via external transfer. Results: 104 patients with a mean age of 59.7 ± 15.3 years were included, 53.2% being male, with 49% being hypertensive and 79.8% denying smoking. There was not any statistical significance between sedative drugs for the onset of delirium. Most patients with delirium were in the FSS range between 0-15 in the intensive care unit setting and 16-25 in the infirmaries. Final considerations: There is no association between the use of drugs with sedative action and delirium. There was a change in the functional profile, with patients becoming moderate to maximum dependents in the intensive care units and minimize or independent dependents in the wards.